Una consideración histórico-didáctica de matemática elemental - Aznar Garcia, J. V. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper is a description and a critical study to the work signed by Ventura Reyes Prosper (1863-1922) in the Archivo de Matemáticas Puras y Aplicadas, «A new demonstration of the trigonometrical formulae of an angle equal to addition or substraction of two angles » claiming the applications of the Matematics History of M. to critical education.